Evaluating the Factors Affecting COVID-19 Patients’ Mortality in Arak in 2020 - Hossein Mazaherpour; Masoumeh Soofian; Elham Farahani; Ahmad Saebbian; Mostafa Etebari; Sakineh Mazaherpour; Fatemeh Ashrafian; Amitis Ramezani (Canadian Respiratory Journal)
Background. The coronavirus disease 2019 (COVID-19) pandemic has been a leading cause of death in the world in the last few years. This study has investigated various causes and risk factors that may lead to death due to this disease. Methods. From June to October 2020, 98 expired and 196 recovered patients were studied for risk factors, underlying diseases, and laboratory findings that could lead to disease progression and mortality. Results. There was a significant relationship in terms of blood pressure, age, oxygen saturation, tachycardia, tachypnea, the interval between the onset of symptoms and hospitalization, diabetes mellitus, lung disease, cardiovascular disease, history of opium abuse, C-reactive protein, white blood cell, lymphocytes, hemoglobin, creatinine elevation, elevated liver enzyme, creatine phosphokinase, lactate dehydrogenase, ferritin, D-dimer, troponin, prothrombin time, international normalized ratio, intensive care unit admission days, arrhythmia, sepsis, acute respiratory distress syndrome, acute kidney injury (AKI), and the type of antiviral and antibiotic therapy between the two groups of patients. Conclusions. Mortality due to COVID-19 is affected by various causes such as age, underlying diseases, and complications that may occur in the course of the disease (e.g., arrhythmia, myocardial infarction, and AKI). By accurately identifying these causes and risk factors, we can prevent these complications and the mortality from COVID-19.